Investigating environmental quality and economic growth interdependency: an environmental kuznets curve study of South Africa - Padayachee, Bradley (Graduate School of Business (GSB), 2026)
Economic growth at the expense of environmental quality has become an increasingly important policy concern since 2015, with the establishment of the Sustainable Development Goals at the United Nations Framework Convention on Climate Change in Paris. This study investigated the interdependency between environmental quality and economic growth in South Africa, within the framework of the Environmental Kuznets Curve (EKC) hypothesis, based on annual emissions and economic growth data from 1970 to 2018. The study examined the short and long run relationships of CO2, NO2, SO2 and PM2.5 emissions with economic growth, respectively, utilising a time-series Autoregressive Distributed Lag estimation method in conjunction with classical unit root and cointegration techniques. The study revealed that CO2, NO2 and PM2.5 has positive and statistically significant long run relationships with economic growth in South Africa. Additionally, CO2 was found to be the only indicator of environmental quality that depicted a negative and significant long run relationship with economic growth squared, thereby revealing a negative parabolic relationship with economic growth in accordance with the Environmental Kuznets hypothesis. Similarly, only CO2 emissions portrayed an EKC relationship with economic growth in the short run, while NO2 and PM2.5 were found to have linear relationships with economic growth. Overall, only CO2 was found to have a valid EKC relationship with economic growth in the long and short run for South Africa. The result reveals that incremental economic growth may result in diminishing CO2 emissions as the country transitions from an industrial to a service-oriented economy. This result is linked to South Africa's reliance on coal for energy, its energy-intensive industrial economy, and the foundational relationship between these factors and economic growth. The study recommends that South Africa explores policies aimed at enhanced emissions monitoring and improved regulatory threshold enforcement. Despite the results, the country should also seek to further diversify its energy sector and explore less carbon intensive alternatives without foregoing energy security.